Authentic leadership: What's in the construct? - Nada Endrissat; Werner R. Müller (Universität Basel, Wirtschaftswissenschaftliches Zentrum (WWZ), 2006)
In a qualitative leadership study conducted in the German-speaking part of Switzerland the quest to be oneself i.e., to be authentic was found to be central for leadership. We will present the results in detail and highlight the difficulties leaders experience when trying to be authentic in their daily interaction. By providing a contextually rich description of authentic leadership from practitioners' point of views, our study contributes to the current endeavor to understand and define authentic leadership. We compare our results with popular theorizing and outline implications for the future study of authentic leadership.
Keywords: 330